Dexmedetomidine as a Rescue Therapy for Emergence Delirium in Adults: A Case Series. Issue 1 (1st July 2017) - Read, Matthew D.; Maani, Christopher V.; Blackwell, Scott
Abstract : Emergence delirium (ED) in adult patients encountered in the postanesthesia care unit (PACU) is not well studied; nor are ED treatment strategies. Similar to delirium in the intensive care unit, ED in the PACU can result in serious complications. We describe 3 cases of ED in the PACU in patients with a history of posttraumatic stress disorder who were successfully treated with dexmedetomidine. Although likely utilized more frequently in recent years, the use of dexmedetomidine in the PACU for treatment of ED is not established in the literature. Further research regarding treatment of ED in adults is necessary, allowing for optimization of patient care and improvement in patient outcomes.